Targeting TGFβ with chimeric switch receptor and secreted trap to improve T cells anti-tumor activity - Matikhina, Tatyana; Cohen, Cyrille J. (Frontiers in Immunology, 2024)
Introduction: TGFβ is a major immunoinhibitory factor present in the microenvironment of solid tumors. Various cancer types acquire the ability to overexpress TGFβ to escape immune response. Specifically, TGFβ dampens cytotoxic T cell activity, and its presence has been correlated with tumor invasion and poor prognosis. Methods: In this study, we developed two approaches to counteract the effects of TGFβ and provide a functional advantage to genetically engineered T cells in the immunoinhibitory tumor milieu. We designed a TGFβRI-based co-stimulatory switch receptor (CSRI), comprising the TGFβ receptor I extracellular binding domain and a 4-1BB co-stimulatory signaling moiety. Additionally, we tested the efficacy of a TGFβ-binding scFv trap produced by T cells. Results: We demonstrated that both approaches enhanced tumor-specific T cell cytokine secretion, upregulated activation markers, and reduced inhibition markers upon co-culture with melanoma targets. Furthermore, CSRI and the anti-TGFβ trap exhibited improved anti-tumor function in vivo. Conclusion: Overall, we show that targeting the TGFβ pathway can enhance cellular immunotherapy.